BCL-XL directly modulates RAS signalling to favour cancer cell stemness. Issue 1 (December 2017) - Carné Trécesson, Sophie; Souazé, Frédérique; Basseville, Agnès; Bernard, Anne-Charlotte; Pécot, Jessie; Lopez, Jonathan; Bessou, Margaux; Sarosiek, Kristopher; Letai, Anthony; Barillé-Nion, Sophie; Valo, Isabelle; Coqueret, Olivier; et al.
Abstract In tumours, accumulation of chemoresistant cells that express high levels of anti-apoptotic proteins such as BCL-XL is thought to result from the counter selection of sensitive, low expresser clones during progression and/or initial treatment. We herein show that BCL-XL expression is selectively advantageous to cancer cell populations even in the absence of pro-apoptotic pressure. In transformed human mammary epithelial cells BCL-XL favours full activation of signalling downstream of constitutively active RAS with which it interacts in a BH4-dependent manner. Comparative proteomic analysis and functional assays indicate that this is critical for RAS-induced expression of stemness regulators and maintenance of a cancer initiating cell (CIC) phenotype. Resistant cancer cells thus arise from a positive selection driven by BCL-XL modulation of RAS-induced self-renewal, and during which apoptotic resistance is not necessarily the directly selected trait. BCL-XL provides a survival advantage to cancer cells even in the absence of apoptotic pressures. In this study, the authors show that BCL-XL interacts with RAS in a BH4-dependent manner and regulates RAS-mediated activation of pathways involved in the stemness feature of breast cancer cells.